Duration of Treatment Effect Using IncobotulinumtoxinA for Upper-limb Spasticity: A Post-hoc Analysis - Kaňovský, Petr; Elovic, Elie P.; Hanschmann, Angelika; Pulte, Irena; Althaus, Michael; Hiersemenzel, Reinhard; Marciniak, Christina (Frontiers in Neurology, 2021)
The efficacy and safety of incobotulinumtoxinA ≤400 U was demonstrated in subjects with post-stroke upper-limb spasticity in a randomized, double-blind Phase 3 study with an open-label extension (OLEX; EudraCT number 2005-003951-11, NCT00432666). We report a post-hoc analysis of the duration of the treatment effect. Subjects completing the placebo-controlled main period (single injection cycle with 12–20-week observation) entered the OLEX and received a maximum of five further treatments (maximum duration 69 weeks) with incobotulinumtoxinA ≤400 U at flexible intervals with a minimum duration of 12 weeks, based on clinical need. Intervals between two consecutive incobotulinumtoxinA injections, excluding treatment intervals prior to the end-of-study visit, were evaluated. Of 437 incobotulinumtoxinA treatment intervals, 415 received by 136 subjects were included in the post-hoc analysis. More than half (52.3%; 217/415) of all incobotulinumtoxinA reinjections were administered at Week ≥14, 31.1% (129/415) at Week ≥16, 19.0% (79/415) at Week ≥18, and 11.6% (48/415) at Week ≥20. The duration of effect may vary and can exceed 20 weeks or more, which was observed in at least one injection cycle in 29.4% (40/136) subjects over the course of their treatment. Data show that incobotulinumtoxinA retreatment for upper-limb spasticity may not be required at 12-week intervals and provides evidence for flexible treatment intervals beyond this time frame.